Manned spacecraft design principles - Sforza, P. M. (Elsevier, 2016)
This book presents readers with a brief, to-the-point primer that includes a detailed introduction to the information required at the preliminary design stage of a manned space transportation system. In the process of developing the preliminary design, the book covers content not often discussed in a standard aerospace curriculum, including atmospheric entry dynamics, space launch dynamics, hypersonic flow fields, hypersonic heat transfer and skin friction, along with the economic aspects of space flight. Key concepts relating to human factors and crew support systems are also included, providing users with a comprehensive guide on how to make informed choices from an array of competing options. The book can be used in conjunction with Sforza's, Commercial Aircraft Design Principles to form a complete course in Aircraft/Spacecraft Design.
Keywords: Manned space flight -- Systems engineering.; Astronautics.; elektronické knihy; electronic books